ATF3 Positively Regulates Antibacterial Immunity by Modulating Macrophage Killing and Migration Functions - Du, Yuzhang; Ma, Zhihui; Zheng, Juanjuan; Huang, Shu; Yang, Xiaobao; Song, Yue; Dong, Danfeng; Shi, Liyun; Xu, Dakang (Frontiers in Immunology, 2022)
The clinical severity of Staphylococcus aureus (S. aureus) respiratory infection correlates with antibacterial gene signature. S. aureus infection induces the expression of an antibacterial gene, as well as a central stress response gene, thus activating transcription factor 3 (ATF3). ATF3-deficient mice have attenuated protection against lethal S. aureus pneumonia and have a higher bacterial load. We tested the hypothesis that ATF3-related protection is based on the increased function of macrophages. Primary marrow-derived macrophages (BMDM) were used in vitro to determine the mechanism through which ATF3 alters the bacterial-killing ability. The expression of ATF3 correlated with the expression of antibacterial genes. Mechanistic studies showed that ATF3 upregulated antibacterial genes, while ATF3-deficient cells and lung tissues had a reduced level of antibacterial genes, which was accompanied by changes in the antibacterial process. We identified multiple ATF3 regulatory elements in the antibacterial gene promoters by chromatin immunoprecipitation analysis. In addition, Wild type (WT) mice had higher F4/80 macrophage migration in the lungs compared to ATF3-null mice, which may correlate with actin filament severing through ATF3-targeted actin-modifying protein gelsolin (GSN) for the macrophage cellular motility. Furthermore, ATF3 positively regulated inflammatory cytokines IL-6 and IL-12p40 might able to contribute to the infection resolution. These data demonstrate a mechanism utilized by S. aureus to induce ATF3 to regulate antibacterial genes for antimicrobial processes within the cell, and to specifically regulate the actin cytoskeleton of F4/80 macrophages for their migration.